Measuring the impact of clean energy production on CO2 abatement in Denmark: Upper bound estimation and forecasting. (1st November 2020) - Christensen, Bent Jesper; Datta Gupta, Nabanita; Santucci de Magistris, Paolo
Abstract: Using annual data from 1978 through 2016, and monthly data from January 2005 through November 2017 from Denmark, we provide a precise estimate of the upper bound on the potential impact of the adoption of wind energy on the reduction of CO 2 emissions from energy production. We separate causal impacts from endogenous effects in regressions using instrumental variables including average wind speed, and from spurious effects in dynamic systems using impulse‐response analysis and cointegration techniques. A one percentage point increase in the share of wind in total energy production is found to cause a reduction in CO 2 emissions of the order 0.3%, based on endogeneity‐corrected regression, and 0.5% over 2 years in a fractional vector error‐correction model, after allowing the cumulative effects to take place. This corresponds to an upper bound estimate of 0.69 tonnes of CO 2 emissions avoided per additional MWh of wind energy produced. We find that after a structural break at the time of introduction of the EU ETS and the Kyoto Protocol in 2005, the country has been on track towards meeting its long‐term goals for emission reduction and green energy production, but not before.